The importance of peers for compliance with norms of fair sharing - Gaechter, Simon; Gerhards, Leonie; Nosenzo, Daniele (Elsevier, 2017)
A burgeoning literature in economics has started examining the role of social norms in explaining economic behavior. Surprisingly, the vast majority of this literature has studied social norms in asocial decision settings, where individuals are observed to act in isolation from each other. In this paper we use a large-scale dictator game experiment (N = 850) to show that “peers” can have a profound influence on individuals’ perceptions of norms of fair sharing, which we elicit in an incentive compatible way. However, in contrast to these strong peer effects in social norms of fair sharing, we find limited evidence of the influence of norms and peers on actual sharing behavior. We discuss how these results can be explained by heterogeneity in normative views as well as in willingness to comply with norms.